Show Posts

This section allows you to view all posts made by this member. Note that you can only see posts made in areas you currently have access to.

Messages - Ye Jin

Pages: [1]
1
Term Test 2 / Re: TT2A Problem 5
« on: November 24, 2018, 08:35:43 AM »
$f(z)=\frac{2}{z-2}+\frac{1}{z+1}$

(a) |z|<1

$f(z)= \frac{1}{\frac{z}{2}-1}$+$\frac{1}{z+1}$

$= \sum_{n=0}^{\infty}-(\frac{z}{2})^n+(-z)^n$

$= \sum_{n=0}^{\infty}\frac{-z^n}{2^n}+(-1)^nz^n$

$= \sum_{n=0}^{\infty} (\frac{-1}{2^n}+(-1)^n)z^n$

(b) 1<|z|<2

$f(z)= \frac{1}{\frac{z}{2}-1}$+$\frac{1}{z}\frac{1}{1+\frac{1}{z}}$

$= \sum_{n=0}^{\infty} -(\frac{z}{2})^n+\sum_{n=0}^{\infty}\frac{1}{z}(\frac{-1}{z})^n$

$= \sum_{n=0}^{\infty}\frac{-z^n}{2^n}+\sum_{n=0}^{\infty}\frac{(-1)^n}{z^{n+1}}$

$= \sum_{n=0}^{\infty}\frac{-z^n}{2^n}+\sum_{n=1}^{\infty}\frac{(-1)^{n-1}}{z^{n}}$

$= \sum_{n=0}^{\infty}\frac{-1}{2^n}z^n+\sum_{n=-\infty}^{1}(-1)^{-n-1}z^{n}$

(c)|z|>2

$f(z)= \frac{2}{z}\frac{1}{1-\frac{2}{z}}$+$\frac{1}{z}\frac{1}{1+\frac{1}{z}}$

$=\sum_{n=0}^{\infty}\frac{2}{z}(\frac{2}{z})^n+\frac{1}{z}(\frac{-1}{z})^n$

$=\sum_{n=0}^{\infty}\frac{2^{n+1}}{z^{n+1}}+\frac{(-1)^n}{z^{n+1}}$

$=\sum_{n=-\infty}^{0}(2^{n+1}+(-1)^n)z^{n-1}$

$=\sum_{n=-\infty}^{1}(2^{n+2}+(-1)^{n+1})z^{n}$

2
Reading Week Bonus--sample problems for TT2 / Re: Term Test 2 sample P5
« on: November 09, 2018, 10:56:09 AM »
Calculate the coefficient at $z^{-2}$. The answer is rather obvious because $f(z)$ decays as $z^{-4}$ as $z\to \infty$
So I should start from n=-1 because the coefficient is 0 when n=0?
While starting from the term with $0$ coefficient is not technically an error, it is definitely a bad bad practice.
And now is there any other mistake I have made?

3
Reading Week Bonus--sample problems for TT2 / Re: Term Test 2 sample P5
« on: November 09, 2018, 10:30:36 AM »
Calculate the coefficient at $z^{-2}$. The answer is rather obvious because $f(z)$ decays as $z^{-4}$ as $z\to \infty$
So I should start from n=-1 because the coefficient is 0 when n=0?

4
Reading Week Bonus--sample problems for TT2 / Re: Term Test 2 sample P5
« on: November 09, 2018, 09:46:03 AM »
I have modified but for |z|>5, the largest power I got is -2.

5
Reading Week Bonus--sample problems for TT2 / Re: Term Test 2 sample P5
« on: November 08, 2018, 12:19:47 PM »
Let $w=z^2$, then $f(w)=\frac{16}{(w-16)(w+25)}$

$=\frac{16}{41}\frac{1}{w-16}-\frac{16}{41}\frac{1}{w+25}$

plug $w=z^2$, $f(z)=\frac{16}{41}\frac{1}{z^2-16}-\frac{16}{41}\frac{1}{z^2+25}$

(a) $|z|<4 ,so |w|<16$

$f(w)=\frac{1}{41} \frac{1}{-1+\frac{w}{16}}-\frac{16}{41\cdot25} \frac{1}{1-\frac{-w}{25}}$

$=\frac{-1}{41}\sum_{n=0}^{\infty}(\frac{w}{41})^n-\frac{16}{41\cdot25}\sum_{n=0}^{\infty}(\frac{-w}{25})^n$

$=\sum_{n=0}^{\infty}(\frac{-1}{41\cdot16^n}-\frac{(-1)^n16}{41\cdot25^{n+1}}\,){w}^n$

$f(z)=\sum_{n=0}^{\infty}(\frac{-1}{41\cdot16^n}-\frac{(-1)^n16}{41\cdot25^{n+1}}\,)z^{2n}$

(b) $4<|z|<5 ,so 16<|w|<25$

$f(w)=\frac{16}{41w} \frac{1}{1-\frac{16}{w}}-\frac{16}{41\cdot25} \frac{1}{1-\frac{-w}{25}}$

$=\frac{16}{41w}\sum_{n=0}^{\infty}(\frac{16}{w})^n-\frac{16}{41\cdot25} \sum_{n=0}^{\infty}(\frac{-w}{25})^n$

$=\sum_{n=0}^{\infty}\frac{16^{n+1}}{41w^{n+1}}- (\frac{(-1)^n16}{41\cdot25^{n+1}}\,){w}^n$

$= \sum_{n=1}^{\infty} \frac{16^n}{41w^n}- (\frac{(-1)^n16}{41\cdot25^{n+1}}\,){w}^n$

$=\sum_{n=-\infty}^{-1} \frac{16^{-n}}{41}w^n-\sum_{n=0}^{\infty}(\frac{(-1)^n16}{41\cdot25^{n+1}}\,){w}^n$

$f(z)=\sum_{n=-\infty}^{-1} \frac{16^{-n}}{41}z^{2n}-\sum_{n=0}^{\infty}(\frac{(-1)^n16}{41\cdot25^{n+1}}\,)z^{2n}$

(c) $5<|z| ,so 25<|w|$

$f(w)=\frac{16}{41w} \frac{1}{1-\frac{16}{w}}-\frac{16}{41w} \frac{1}{1-\frac{-25}{w}}$

$=\frac{16}{41w}\sum_{n=0}^{\infty}(\frac{16}{w})^n- \sum_{n=0}^{\infty} \frac{16}{41w}(\frac{-25}{w})^n$

$= \sum_{n=0}^{\infty}\frac{16^{n+1}}{41w^{n+1}}-\sum_{n=0}^{\infty} \frac{16(-25)^n}{41w^{n+1}}$

$= \sum_{n=0}^{\infty} (\frac{16^{n+1}}{41}-\frac{16(-25)^n}{41})w^{-n-1}$

$= \sum_{n=-\infty}^{0} (\frac{16^{-n+1}}{41}-\frac{16(-25)^{-n}}{41})w^{n-1}$

$f(z)= \sum_{n=-\infty}^{-1} (\frac{16^{-n+1}}{41}-\frac{16(-25)^{-n}}{41})z^{2n-2}$

6
Term Test 1 / Re: TT1 Problem 3 (noon)
« on: October 19, 2018, 09:41:04 AM »
(a) WTS $v_{xx} + v_{yy}=0$
$v_x = e^xsiny+xe^xsiny+ye^xcosy$, $v_{xx}=e^xsiny+e^xsiny+xe^xsiny+ye^xcosy$
$v_y =xe^xcosy+e^xcosy-ye^xsiny$, $v_{yy}=-xe^xsiny-e^xsiny-e^xsiny-ye^xcosy$
so, $v_{xx} + v_{yy}=0$

(b) Since v is harmonic, then it is analytic.
$v_x=u_y, -v_y=u_x$
$u=\int v_x dy=\int e^xsiny+xe^xsiny+ye^xcosy dy$
$= -e^xcosy-xe^xcosy+e^x(ysiny+cosy)+h(x)$
$u_x=-e^xcosy-e^xcosy-xe^xcosy+e^x(ysiny+cosy)+h^{'}(x)$
$=-e^xcosy-xe^xcosy+e^xysiny+h^{'}x$
so,$-xe^xcosy-e^xcosy+ye^xsiny=-e^xcosy-xe^xcosy+e^xysiny+h^{'}(x)$
so, $h^{'}(x)=0$
h(x)=c
$u=-xe^xcosy+e^xysiny+c$

(c) $f(z)=u+iv= -xe^xcosy+e^xysiny+c+ixe^xsiny+iye^xcosy$
$=-e^xcosy(x-iy)+e^xsiny(y+ix)+c$
$=-e^xcos(y)\bar{z}+e^xsin(y)i\bar{z}+c$
$=\bar{z}e^x(cosy+isiny)+c$
$=\bar{z}e^{Rez}e^{Imz}+c$
$=\bar{z}e^z+c$

7
Quiz-2 / Re: Q2 TUT 0102
« on: October 05, 2018, 06:54:08 PM »
Since\begin{equation*} |z|^2=x^2+y^2\end{equation*},
then  \begin{equation*}g(z)= \frac{1}{[1-(x^2+y^2)]^3}\end{equation*}
Hence, g(z) is not continuous at all points of circle \begin{equation*}x^2+y^2=1\end{equation*}

8
Quiz-1 / Re: Q1: TUT 0101 and TUT 0102
« on: September 28, 2018, 04:36:18 PM »
|x+yi-i|=Rez
|x+(y-1)i|=x
Square Root [x^2+(y-1)^2]=x
x^2 + (y-1)^2=x^2
(y-1)^2=0
So, y=1

Pages: [1]